The effect of the arrangements law on patient mix in Israeli private healthcare - Barnea, Royi; Goldshtein, Hadar; Niv-Yagoda, Adi (Frontiers in Public Health, 2025)
IntroductionHealth inequalities remain a persistent challenge, yet little is known about how financing reforms affect access within private hospitals. In 2016 Israel introduced the shorten waiting times reform, designed to expand publicly financed surgeries and reduce reliance on supplementary and private insurance.MethodsThis study examined its impact on both the financing mix and the socioeconomic composition of surgical patients. Administrative data on 1,082,685 procedures performed at Assuta Medical Centers between 2015 and 2019 were analyzed, comparing pre-reform (2015- October 2017) and post-reform (November 2017-2019) periods, with ambulatory procedures serving as a control group.ResultsPublicly financed surgeries increased from 5% to 51% (ATT +51.6pp; 95% CI 43.3-59.9; p < 0.001), while supplementary and private financing declined. The share of middle-SES patients rose from 52% to 57% (+7.1pp), high-SES declined from 35% to 29% (−8.0pp), and low-SES increased modestly from 13% to 14% (+0.9pp). In contrast, the control group showed only minimal changes.DiscussionThese findings indicate that the reform was associated with a substantial reallocation of financing and a measurable broadening of SES representation, particularly for middle-income groups, with incremental gains for disadvantaged populations. Overall, the results are consistent with improved equity in access and highlight how regulatory tools can harness private capacity for public benefit within a universal health system.